Comparative study of epidural 0.2% ropivacine and fentanyl with 0.2% levobupivacine and fentanyl for postoperative pain relief for modified radical mastectomy - Swathi Gajji; R.Rajeshwar Reddy (International Journal of Health and Clinical Research, 2022)
Background: Effective pain control is crucial for optimal care of surgical patients.Effective post operative analgesia results in decreased stress response and also reduces risk of recurrence and metastasis in cancer patients.Epidural anaesthesia offers most post operative pain relief compared with systemic drugs.Thoracic epidural analgesia is most effective in reducing pain after thoracic and upper abdominal surgeries.In this study,thoracic epidural technique is chosen for post operative management of patients undergoing modified radical mastectomy procedure. Aims and objectives: To compare the analgesic efficacy and adverse effects after adding 0.2%Ropivacine and 0.2%Levobupivacine with Fentanyl when administered post operatively in thoracic epidural infusion for post operative pain relief. Methodology: This is a prospective randomised clinical study, approved by the institutional ethical committee.An individual consent was taken from all patients selected for the study. Total 100 adult female patients undergoing modified radical mastectomy were divided into 2 groups with 50 patients in each group.All patients belonging to ASA grade III.Patients with contraindication for epidural anaesthesia were excluded. Discussion: Thoracic Epidural analgesia offers effective postoperative pain relief for patients undergoing oncological breast surgeries.In this study we are comparing the local anaesthetics Levobupivacine and Ropivacineincombination with Fentanyl for epidural analgesia for modified radical mastectomy. Conclusion: Ropivacaine 0.2% and Levobupivacaine 0.2% concentration when combined with fentanyl were found out to be equally effective in providing postoperative pain relief with no rescue analgesic consumption, but with a significant higher incidence of hemodynamic side effects and motor blockade noted in Levobupivacaine group,which were easily manageable. There was no significant difference in sedation level and other adverse effects.